2015
DOI: 10.1016/j.brat.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A potential pathway to the relapse of fear? Conditioned negative stimulus evaluation (but not physiological responding) resists instructed extinction

Abstract: Relapse of fear after successful intervention is a major problem in clinical practice. However, little is known about how it is mediated. The current study investigated the effects of instructed extinction and removal of the shock electrode on electrodermal responding (Experiment 1), fear potentiated startle (Experiment 2), and a continuous self-report measure of conditional stimulus valence (Experiments 1 and 2) in human differential fear conditioning. Instructed extinction and removal of the shock electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 43 publications
10
46
0
Order By: Relevance
“…Operant conditioning differs from classical conditioning in that it concerns learning associations between responses and their outcomes, rather than associations between stimuli. 20 First, we successfully showed the acquisition of fear of movement-related pain, both in the self-reported fear and painexpectancy ratings, thus providing support for our first hypothesis. Participants in the Experimental Group picked up on the response-outcome contingencies, that is, they learned to expect the pain more when performing T1 than T2, and they expected the pain more when performing T2 than T3.…”
Section: Discussionsupporting
confidence: 51%
“…Operant conditioning differs from classical conditioning in that it concerns learning associations between responses and their outcomes, rather than associations between stimuli. 20 First, we successfully showed the acquisition of fear of movement-related pain, both in the self-reported fear and painexpectancy ratings, thus providing support for our first hypothesis. Participants in the Experimental Group picked up on the response-outcome contingencies, that is, they learned to expect the pain more when performing T1 than T2, and they expected the pain more when performing T2 than T3.…”
Section: Discussionsupporting
confidence: 51%
“…Common examples include situations in which US occurrence is correctly believed to be modulated, but acquired (dis)liking is not (Baeyens, Crombez, De Houwer, & Eelen, 1996;Baeyens, Hendrickx, Crombez, & Hermans, 1998), and situations in which US occurrence is no longer expected due to extinction training, but conditional (dis)liking nonetheless persists (Vansteenwegen, Francken, Vervliet, De Clercq, & Eelen, 2006). A recent study also found that acquired valence (but not physiological responses including fear potentiated startle) resists instructed extinction (Luck & Lipp, 2015). The observation that results were different for the shock expectancy and valence ratings may suggest that different mechanisms are involved, with generalisation of valence conditioning being better explained by traditional association formation theories and falling out of scope of the rule learning mechanism (for a similar argument see Baeyens et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…However, in a recent study by Luck and Lipp (2015a), in which instructed extinction was combined with removal of the shock electrodes, a complete reduction of both SCRs and FPS was observed. As argued by Luck and Lipp (2015b), the incomplete reduction of FPS in the study of Sevenster et al (2012a) can perhaps be explained by a subset of participants in their experiment that did not find the extinction instructions believable (because the shock electrodes remained attached in the study of Sevenster et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%